(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
درسنا امتزاز أزرق الميتيلين واليود من محاليلهما المائية على عينة من الزيوليت السوري عند درجة الحرارة 298 0K. يكون منحني الامتزاز لأزرق الميتيلين من النوع اللانغمويري وينتمي إلى الصنف L حسب تصنيف جيليس وزملائه، بينما ينتمي منحني امتزاز اليود إلى الصنف C حسب التصنيف السابق. بلغت سعة الامتزاز Xm للعينة الزيوليتية المستخدمة 48.23mg/g بالنسبة لأزرق الميتيلين و 55.33mg/g بالنسبة لليود. أما المساحة السطحية المتقبلة لجزيئات أزرق الميتيلين فكانت SMB=93m2/g أما بالنسبة لليود فكانت SI=55.5m2/g. تبين النتائج التي حصلنا عليها إمكانية استخدام الخامات الزيوليتية السورية كمادة مازة لإزالة الألوان والصباغات والمركبات اللاعضوية من محاليلها بكفاءة جيدة، مما يفتح المجال واسعاً للاستفادة من هذه الخامات الوطنية في مجال دعم عملية التنمية في القطر العربي السوري. Adsorption of methylen blue (MB) and iodine(I2) were studied at 298oK, using Syrian zeolite as adsorbent. Adsorption isotherm for MB is Langmuir type and belongs to L-class of Giles classification, and the adsorption isotherm for iodine belongs to C-class .Adsorption capacity of zeolite sample equals 48.23mg/g for MB and 55.33mg/g for I2. Accepting surface area is 93 m2/g for MB molecules, and 55.5m2/g in the case of iodine. The results obtained show that the Syrian zeolite may be used as adsorbent in processes of adsorption from solution to remove colors, dyes and inorganic compounds. These results encourage utilizing Syrian zeolite to support promotion process in Syria